Scarcity of feed raw materials for poultry production in Nigeria: the way-out (2013)
Poultry farmers often turn to use of alternative feed ingredients whenever the prices of the conventional ones skyrocket. Studies have however shown that the performance of poultry birds based on alternative ingredients do not often compare favourably with birds fed conventional ingredients. In addition, in as much as, there is competition between humans and livestock for these feed ingredients (especially maize and soyabean), the pressure will persist. Instead of dissipating so much effort on search of alternatives, the poultry farmer should be encouraged to increase the efficiency of production by considering proper manipulation of feed, application of appropriate housing System and the use of feed additives.